Analysis of consumer behavior factors on willingness to buy chicken meat with halal labels at traditional markets in Jember area - Rizkina, Fitriana Dina; Aulia, Anisa Nurina; Muliasari, Risa Martha; Takenouchi, Naruhito (Universitas Muhammadiyah Mataram, 2022)
Chicken meat is one of the most popular staple foods, but the halal aspect is the main requirement. In traditional markets, chicken is sold without a halal label. This research aimed to analyze the consumer behavior factors on willingness to buy halal chicken meat at traditional markets in Jember Region. This study hypothesizes that consumer behavior factors affect the behavior of willingness to buy chicken meat with a halal label in traditional markets. This study uses survey data from distributing questionnaires to 110 respondents. Multivariate statistical methods do the hypothesis testing technique with SEM Model. The data processing results show that behavioral control and religious commitment variables significantly influence behavior toward buying chicken meat with the halal label. Suggestions based on research results: first, raising awareness about consuming halal-labeled chicken meat is necessary to increase a person's knowledge. Second, it is required to increase the role of the community and the government, both internally and externally, in educating a person's behavior toward consuming chicken meat labeled halal.